Hubungan Menonton Video Youtube Dengan Kemampuan Komunikasi Anak Usia 5 -6 Tahun - Siti Amaliah; Kristiana Maryani; Siti Khosiah (UIN Sultan Maulana Hasanuddin Banten, 2022)
Communication is a variety of opinions and emotions. Communication is used by: code, reaction, verbal and nonverbal, but communication is very familiar in the form of speech. The media that children are most interested in is YouTube, usually YouTube videos are made up of mixture of pictures and songs that children like the most. This study aims to determine wheter there is a relationship between watching YouTube videos and the communication skills of children aged 5-6 years in Ketileng Village, Cilegon District, Cilegon City-Banten. The method used in this study is quantitative correlation, sampling using purposive sampling with a sample of 46 children in early childhood education institutions Ketileng Village. The results of this study indicate that thevalueofsig(2-tailed) is 0.001<0.005, so it can be concluded that there is a relationship between watching YouTube videos and the communication skills of children aged 5-6 years in Ketileng Village, Cilegon District, Cilegon City-Banten. With a correlation value of 0.0469 means that it has a stong relationship watching YouTube videos with the communication skills of children aged 5-6 years. Keywords: communication skills, watching YouTube videos, children aged 5-6 years References Andika, Y., & Sunarti, V. (2018). Hubungan Antara Komunikasi Keluarga dengan Kemampuan Bicara Anak Usia Dini Desa Rambai. Jurnal Pendidikan Luar Sekolah, 6(4), 547–554. Atin, R., & Priyantoro, D. E. (2021). Pentingnya Penanaman Nilai-Nilai Agama Pada Pendidikan Anak Usia Dini Dalam Perspektif Al-Quran. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(1), 1–16. Damayanti, E., & Nasrul, M. A. (2020). Capaian Perkembangan Fisik Motorik Dan Stimulasinya Pada Anak Usia 3-4 Tahun. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 67–80. Departemen Pendidikan Nasional (Depdiknas). (2003). Undang-udang RI No. 20 Tahun 2003 Tentang Sistem Pendidikan Nasional. pusdiklat.perpusnas.go.id. Departemen Pendidikan Nasional (Depdiknas). (2007). Standar Isi Pendidikan Anak Usia Dini. Pusat Kurikkulum Balitbang Depdiknas 2007. Hamdi, A. S., & Bahruddin, E. (2014). Metode Penelitian Kuantitatif Aplikasi dalam Pendidikan (A. Anas (ed.)). Deepublish. Huliyah, M. (2016). Pengembangan Daya Seni Pada Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 149–164. Imroatun, I. (2018). Alternatif Media Pengembangan Literasi Baca Tulis Berbahasa Nasional bagi Siswa Raudlatul Athfal AH-. Al Hikmah Proceedings on Islamic Early Childhood Education, 1(April), 103–112. Imroatun, I., Widat, F., Fauziddin, M., Farida, S., Maryam, S., & Zulaiha. (2021). Youtube as a Media for Strengthining Character Education in Early Childhood. Journal of Physics: Conference Series, 1779(1), 012064. https://doi.org/10.1088/1742-6596/1779/1/012064 Janah, M. M., Fadhli, M., & Kristiana, D. (2019). Hubungan Intensitas Menonton Youtube dengan Perkembangan Sosial Emosional Anak Usia 5-6 Tahun. Jurnal Ilmiah Maha Siswa Universitas Muhammadiyah Ponorogo, 3(2), 110–116. Mulyani, N. (2019). Pengembangan Kreativitas Anak Usia Dini Melalui Bermain Gerak Dan Lagu Di TK Negeri Pembina Kabupaten Purbalingga. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 4(1), 13–24. Mulyani, Y., & Gracinia, J. (2013). Kemampuan Berbahasa, Sains & Matematika. Elex Media Komputindo. Musfiqon, M. (2012). Panduan Lengkapn Metodologi Penelitian Pendidikan. Prestasi Pustaka. Pujianti, R., Sumardi, S., & Mulyadi, S. (2021). Perkembangan Sosial Emosional Anak Usia 5-6 Tahun Selama Pembelajaran Jarak Jauh Di Raudhatul Athfal. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 117–126. https://doi.org/10.32678/AS-SIBYAN.V6I2.4919 Putra, A., & Patmaningrum, D. A. (2018). Pengaruh Youtube di Smartphone Terhadap Perkembangan Komunikasi Interpersonal Anak. Jurnal Penelitian Komunikasi, 21(2), 159–172. Sugiyono. (2015). Metode Penelitian Pendidikan: Pendekatan Kuantitatif, Kualitatif, dan R&D. Alfabeta. Susanto, A. (2019). Bimbingan & Konseling di Taman Kanak-kanak (A. Susanto (ed.); Ke-1). PRENADAMEDIA GROUP. Sutarti, T., & Astuti, W. (2021). Dampak Media Youtube dalam Proses Pembelajaran dan Pengembangan Kreatifitas Bagi Kaum Milenial. Jurnal Widya Aksara, 26(1), 89–101. Widyaningtyas, W., Shari, D., Saleh, N. R., & Asmara, B. (2021). Menigkatkan Kemampuan Kognitif Mengenal Bentuk Geometri Melalui Media Bahan Alam Batu Pelangi. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(1), 41–52. https://doi.org/10.32678/AS-SIBYAN.V6I1.2940